JAVANESE LANGUAGE MAINTENANCE OF INTERMARRIAGES IN RANTAU UTARA - Matrejo Matrejo; Busmin Gurning; Siti Aisyah Ginting (Universitas Negeri Medan, 2019)
This study deals with the Javanese Language Maintenance of Intermarriages in Rantau Utara. It employed qualitative research design with a case study. This study aims to describe: (1) the factors of language maintenance. It was chosen because many of Javanese people who married with other ethnic. The instruments used of this study were observation, questionnaire and interview. The data were analyzed by using Miles, Huberman and Saldana’s data analysis. The result of the study were found that there were six factors of Javanese language of maintaining the language namely seeing each other frequently (100%), neighborhood domain (97%), ethno linguistic vitality (100%), family domain (99%), religion domain (55%) and practice the traditional ceremony (35%). Keywords:Maintanance, Javanese, Language, Intermarriages